2020
DOI: 10.3397/1/376840
|View full text |Cite
|
Sign up to set email alerts
|

Active noise control for centrifugal and axial fans

Abstract: Fans are widely used in industry for heat dissipation or airflow production. It is achieved by driving a motor of fan to rotate a number of blades. Most industrial fans can be categorized into one of two general types: centrifugal fans and axial fans. However, fan noise is loud when the motor speed is high. This article develops using active noise control (ANC) system to reduce noise from both centrifugal and axial fans. By integrating loudspeakers and microphones, we present multiple-channel feedback ANC str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…A study in Korea found the prevalence of Grave's disease to be 2.76 per 1,000 people. [31] In contrast, a study in the United Kingdom found a prevalence rate of early onset Grave's disease in adults to be 24.8 per 100 000. [32] Diabetes insipidus (DI) has a prevalence rate of 1 per 25 000 people.…”
Section: Classmentioning
confidence: 94%
“…A study in Korea found the prevalence of Grave's disease to be 2.76 per 1,000 people. [31] In contrast, a study in the United Kingdom found a prevalence rate of early onset Grave's disease in adults to be 24.8 per 100 000. [32] Diabetes insipidus (DI) has a prevalence rate of 1 per 25 000 people.…”
Section: Classmentioning
confidence: 94%
“…The formula is as follows: xi=XitruenormalXi¯=xi1xi2xin After the sequence normalization is completed, the sequence difference, the two‐pole maximum difference, and the two‐pole minimum difference of all sequences are obtained. [ 26 ] The difference sequence is as follows: ik=normalx0kxik,k=1,2,n i=i1i2in The maximum difference between the two poles and the minimum difference between the two poles are as follows: Smax=maximaxkik Smin=miniminkik …”
Section: Data‐driven Energy Savings Bottleneck Diagnosis Methodsmentioning
confidence: 99%
“…47 However, non-phagocytic cells also show uptake of anionic particles and have been related to the biological effects. 48,49 For example, the HA particles undergo cell internalization through receptor-mediated endocytosis by binding to CD44 receptors present on the cell membrane. 16 Previously, we have reported specificity of the HA−PEI and HA−PEI/HA−PEG particles toward the CD44 receptor expressing cells (J774A.1 macrophages, peritoneal macrophages in vivo, and Panc-1, pancreatic cancer cells) and exhibiting transfection of pDNA (IL-4, IL-10, microRNA 155, and microRNA 125b) by showing upregulation of proteins corresponding to the respective plasmids.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%